Activation method of polyacrylonitrile active low-temperature carbon fiber, polyacrylonitrile active carbon fiber and preparation method and application thereof
Patent Information
- Application Number
- CN202310262435.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-03-17
- Publication Date
- 2026-10-13
- Estimated Expiration
- 2043-03-17
AI Technical Summary
[0006]本发明的目的是为了克服现有技术存在的活性碳纤维比表面积低且制备步骤繁琐、力学性能损失较大的问题,提供一种聚丙烯腈活性低温碳纤维的活化方法、聚丙烯腈活性碳纤维及其制备方法与应用,该活化方法将酸处理和超临界二氧化碳处理结合,能够避免高温对纤维的损伤,同时将聚丙烯腈活性低温碳纤维内部溶剂更好排除并且不会造成空洞塌陷,提高最终制备的聚丙烯腈活性碳纤维的比表面积高,减少孔结构对其力学性能的影响程度,进一步使得聚丙烯腈活性碳纤维具有较高的力学性能
[0017]通过上述技术方案,本发明提供的聚丙烯腈活性低温碳纤维的活化方法、聚丙烯腈活性碳纤维及其制备方法与应用获得以下有益效果:所述活化方法将酸处理和超临界二氧化碳处理相结合,能够避免高温对纤维的损伤,同时将聚丙烯腈活性低温碳纤维内部溶剂更好地排除并且不会造成空洞塌陷,提高最终制备的聚丙烯腈活性碳纤维的比表面积,减少孔结构对其力学性能的影响,进一步使得聚丙烯腈活性碳纤维具有较高的力学性能。
Abstract
Description
Technical Field
[0001] This invention relates to the field of carbon fiber surface modification technology, specifically to an activation method for polyacrylonitrile activated low-temperature carbon fibers, polyacrylonitrile activated carbon fibers, their preparation methods, and applications. Background Technology
[0002] Activated carbon fiber (ACF) shares similar characteristics with activated carbon, such as a large specific surface area and a large number of microporous structures, resulting in superior adsorption performance. At the same time, activated carbon fiber has better mechanical properties and is easier to recycle and reuse than activated carbon. Therefore, it is widely used in wastewater treatment, air purification, hydrogen storage, solvent recovery, medicine, carriers, anti-toxic materials, hydrometallurgy, and other fields.
[0003] The raw materials for preparing activated carbon fibers generally fall into three categories: the first category includes biomass raw materials such as cellulose, plant stems, rice husks, and lignin; the second category includes polymeric raw materials such as polyacrylonitrile, plastics, and resins; and the third category includes heavy carbon raw materials such as mesophase pitch and petroleum coke tar pitch. Among various activated carbon fibers (ACFs), polyacrylonitrile-based ACFs (PAN-ACFs) have a carbon yield exceeding 50% of their original precursor mass, significantly reducing CO2 emissions. Currently, activated carbon fiber preparation methods generally include chemical activation and gas activation. Gas activation methods generally include steam activation, CO2 activation, and air activation. Chemical activation methods generally utilize acids, alkalis, and other substances to react with disordered carbon, thereby forming a microporous structure inside and on the surface of the fiber to prepare activated carbon fibers.
[0004] CN106676676A discloses a method for preparing polyacrylonitrile-based activated carbon fibers and their applications. First, polyacrylonitrile fibers are subjected to a three-stage heat treatment to obtain pre-oxidized fibers. Then, they are carbonized at a low temperature of 600-900℃ in a nitrogen atmosphere. Finally, they are activated for 60-200 minutes in a nitrogen:water vapor volume ratio of 1:1 at a temperature range of 700-1000℃ to obtain the final activated carbon fibers. This activation method is cumbersome and yields activated carbon fibers with a low specific surface area.
[0005] CN103409853A discloses a method for preparing activated carbon fiber materials with energy storage characteristics from polyacrylonitrile-based pre-oxidized fibers and its application. The method involves washing and drying purchased pre-oxidized fibers, followed by activation treatment with a strong alkali. By controlling the water content and heating rate during this process, activated carbon fibers with different degrees of activation are obtained and applied to electrochemical capacitors. This method uses a strong alkali, requiring high-quality equipment and incurring additional costs such as wastewater treatment. The process is relatively complex, and the strong alkali activation process is difficult to control. Summary of the Invention
[0006] The purpose of this invention is to overcome the problems of low specific surface area, cumbersome preparation steps, and significant loss of mechanical properties in existing activated carbon fibers. This invention provides an activation method for polyacrylonitrile activated low-temperature carbon fibers, the activated carbon fibers themselves, their preparation method, and their applications. This activation method combines acid treatment and supercritical carbon dioxide treatment, which avoids damage to the fibers from high temperatures. Simultaneously, it better removes the solvent from the internal structure of the polyacrylonitrile activated low-temperature carbon fibers without causing void collapse, thus increasing the specific surface area of the final prepared polyacrylonitrile activated carbon fibers and reducing the influence of pore structure on their mechanical properties, further resulting in higher mechanical properties for the polyacrylonitrile activated carbon fibers.
[0007] To achieve the above objectives, a first aspect of the present invention provides a method for activating polyacrylonitrile activated low-temperature carbon fibers, characterized in that the method comprises:
[0008] Low-temperature carbon fibers are subjected to acid treatment to obtain pretreated activated low-temperature carbon fibers; the pretreated activated low-temperature carbon fibers are then subjected to supercritical carbon dioxide treatment to obtain polyacrylonitrile activated low-temperature carbon fibers.
[0009] A second aspect of the present invention provides a method for preparing polyacrylonitrile activated carbon fibers, characterized in that the method comprises:
[0010] S1. Polyacrylonitrile spinning solution is spun to obtain polyacrylonitrile fibers, and the polyacrylonitrile fibers are subjected to pre-oxidation treatment and low-temperature carbonization treatment to obtain low-temperature carbon fibers.
[0011] S2. Activate the low-temperature carbon fiber to obtain polyacrylonitrile activated low-temperature carbon fiber;
[0012] S3. The polyacrylonitrile activated low-temperature carbon fiber is subjected to high-temperature carbonization treatment to obtain the polyacrylonitrile activated carbon fiber;
[0013] In step S2, the activation method is the activation method described in the first aspect of the present invention.
[0014] A third aspect of the present invention provides a polyacrylonitrile activated carbon fiber prepared by the method described in the second aspect of the present invention;
[0015] The specific surface area of the polyacrylonitrile activated carbon fiber is 900-2900 m². 2 / g; the single filament strength loss rate of the polyacrylonitrile activated carbon fiber is 0.3%-4% of the single filament strength of the polyacrylonitrile carbon fiber.
[0016] The fourth aspect of this invention provides an application of the polyacrylonitrile activated carbon fiber described in the third aspect in the field of adsorption.
[0017] Through the above technical solutions, the activation method of polyacrylonitrile activated low-temperature carbon fiber, polyacrylonitrile activated carbon fiber and its preparation method and application provided by the present invention achieve the following beneficial effects: The activation method combines acid treatment and supercritical carbon dioxide treatment, which can avoid damage to the fiber by high temperature, and at the same time better remove the solvent inside the polyacrylonitrile activated low-temperature carbon fiber without causing void collapse, thereby increasing the specific surface area of the finally prepared polyacrylonitrile activated carbon fiber, reducing the influence of pore structure on its mechanical properties, and further enabling the polyacrylonitrile activated carbon fiber to have higher mechanical properties. Detailed Implementation
[0018] The endpoints and any values of the ranges disclosed herein are not limited to the precise ranges or values, and these ranges or values should be understood to include values close to these ranges or values. For numerical ranges, the endpoint values of the various ranges, the endpoint values of the various ranges and individual point values, and individual point values can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed herein.
[0019] The first aspect of this invention provides a method for activating polyacrylonitrile activated low-temperature carbon fibers, characterized in that the method comprises:
[0020] Low-temperature carbon fibers are subjected to acid treatment to obtain pretreated activated low-temperature carbon fibers; the pretreated activated low-temperature carbon fibers are then subjected to supercritical carbon dioxide treatment to obtain polyacrylonitrile activated low-temperature carbon fibers.
[0021] According to the present invention, the acid treatment includes contacting the low-temperature carbon fiber with an acid solution.
[0022] In this invention, the contact can be a conventional method in the art, such as soaking or spraying.
[0023] According to the present invention, the contact conditions include: a contact temperature of 5-35°C and a contact time of 5-18 hours.
[0024] According to the present invention, the acid solution is selected from inorganic acid solutions and / or organic acid solutions.
[0025] According to the present invention, the acid solution is selected from at least one of hydrochloric acid solution, phosphoric acid solution and citric acid.
[0026] According to the present invention, the concentration of the acid solution is 0.1-3 g / mL.
[0027] In this invention, the concentration of the acid solution and the contact conditions meet the above-mentioned ranges, which enables the low-temperature carbon fiber to undergo a smooth activation reaction.
[0028] Furthermore, the contact conditions include: a contact temperature of 10-30°C and a contact time of 8-16 hours.
[0029] Furthermore, the concentration of the acid solution is 1-3 g / mL.
[0030] According to the present invention, the supercritical carbon dioxide treatment is carried out in a reaction vessel.
[0031] According to the present invention, the conditions for supercritical carbon dioxide treatment include: a temperature of 50-140°C; a pressure of 8-20 MPa; and a time of 10-50 min.
[0032] In this invention, the conditions for supercritical carbon dioxide treatment meet the above-mentioned range, and together with the acid solution of a specific concentration, the specific surface area of the final prepared polyacrylonitrile activated carbon fiber can be increased, the influence of pore structure on its mechanical properties can be reduced, and the polyacrylonitrile activated carbon fiber can be further made to have higher mechanical properties.
[0033] Furthermore, the conditions for supercritical carbon dioxide treatment include: a temperature of 50-130℃; a pressure of 10-80MPa; and a time of 20-50min.
[0034] According to the present invention, the method further includes: purging the reactor before supercritical carbon dioxide treatment.
[0035] According to the present invention, the conditions for the venting treatment include: passing supercritical carbon dioxide into the reactor 2-5 times, preferably 3-4 times.
[0036] According to the present invention, the method further includes: depressurizing the reactor after supercritical carbon dioxide treatment.
[0037] In this invention, the pressure relief process includes depressurizing the reactor for 1-3 minutes.
[0038] A second aspect of the present invention provides a method for preparing polyacrylonitrile activated carbon fibers, characterized in that the method comprises:
[0039] S1. Polyacrylonitrile spinning solution is spun to obtain polyacrylonitrile fibers, and the polyacrylonitrile fibers are subjected to pre-oxidation treatment and low-temperature carbonization treatment to obtain low-temperature carbon fibers.
[0040] S2. Activate the low-temperature carbon fiber to obtain polyacrylonitrile activated low-temperature carbon fiber;
[0041] S3. The polyacrylonitrile activated low-temperature carbon fiber is subjected to high-temperature carbonization treatment to obtain the polyacrylonitrile activated carbon fiber;
[0042] In step S2, the activation method is the activation method described in the first aspect of the present invention.
[0043] In this invention, there is no particular limitation on the spinning method in step S1. For example, it can be wet spinning or dry-jet wet spinning.
[0044] In this invention, the polyacrylonitrile spinning solution comprises polyacrylonitrile precursor fiber and a solvent. The solid content of the polyacrylonitrile spinning solution is 10-20 wt%.
[0045] In this invention, the solvent includes N,N-dimethylformamide (DMF), dimethyl sulfoxide (DMSO), and dimethylacetamide (DMAc), etc.
[0046] In this invention, when the spinning is wet spinning, the conditions for wet spinning can be conventionally selected in the art, for example: the spinneret orifice diameter is 0.05-0.06 mm, the number of spinneret orifices is 3000-50000, the coagulation bath temperature is 0-10℃, the coagulation bath concentration is 10-24%, the hot drawing can be water bath hot drawing (90-98℃ hot water), and the drawing ratio is 2-20.
[0047] According to the present invention, the pre-oxidation process includes subjecting the polyacrylonitrile fiber to a stepped heating treatment in multiple temperature zones.
[0048] According to the present invention, the polyacrylonitrile fiber passes through four temperature zones, the four temperature zones including a first temperature zone, a second temperature zone, a third temperature zone and a fourth temperature zone.
[0049] According to the present invention, the temperature of the first temperature zone is 210-230°C, the temperature of the second temperature zone is 225-245°C, the temperature of the third temperature zone is 245-265°C, and the temperature of the fourth temperature zone is 265-285°C.
[0050] According to the present invention, the pre-oxidation time of the first temperature zone is 8-12 min, the pre-oxidation time of the second temperature zone is 9-13 min, the pre-oxidation time of the third temperature zone is 13-15 min, and the pre-oxidation time of the fourth temperature zone is 10-15 min.
[0051] According to the present invention, the conditions for the low-temperature carbonization treatment include: a temperature of 300-800℃, preferably 400-800℃, and a heating rate of 5-10℃ / min, preferably 6-9℃ / min.
[0052] According to the present invention, the high-temperature carbonization treatment is carried out in a protective atmosphere.
[0053] In this invention, the protective atmosphere can be N2, Ar, etc.
[0054] According to the present invention, the conditions for high-temperature carbonization include: a temperature of 1200-1600℃, preferably 1400-1600℃, and a heating rate of 5-30℃ / min, preferably 10-30℃ / min.
[0055] According to a particularly preferred embodiment of the present invention, the method includes:
[0056] S1. Polyacrylonitrile fibers are prepared by wet spinning of DMSO / polyacrylonitrile spinning solution with a solid content of 10-20 wt%. The spinneret orifice diameter is 0.05-0.055 mm and the number of spinneret orifices is 2000-3000. The solution is passed through a coagulation bath with a coagulation bath temperature and concentration of 0℃ and 12%, respectively. The hot drawing process is carried out with hot water at 94℃ and the hot drawing ratio is 10 to obtain polyacrylonitrile fibers.
[0057] S2. The polyacrylonitrile fiber is pre-oxidized in an oxidation furnace in four temperature zones: the first temperature zone is 210-230℃, and the pre-oxidation time is 8-12 min; the second temperature zone is 225-245℃, and the pre-oxidation time is 9-13 min; the third temperature zone is 245-265℃, and the pre-oxidation time is 13-15 min; the fourth temperature zone is 265-285℃, and the pre-oxidation time is 10-15 min, to obtain pre-oxidized fiber; the pre-oxidized fiber is then subjected to low-temperature carbonization by heating to 300-800℃ at a heating rate of 5-10℃ / min to obtain low-temperature carbon fiber;
[0058] S3. Soak the low-temperature carbon fiber in an acid solution with a concentration of 0.1-3 g / mL for 5-18 hours, then place it in a reaction vessel, introduce CO2 into the reaction vessel twice at 50-140℃ to remove air, and continue to introduce CO2 until the pressure in the reaction vessel is 8-20 MPa. After treatment for 10-50 minutes, depressurize for 2 minutes to obtain polyacrylonitrile activated low-temperature carbon fiber.
[0059] S4. The polyacrylonitrile activated low-temperature carbon fiber is heated to 1200-1600℃ under N2 atmosphere protection at a heating rate of 5-30℃ / min to obtain polyacrylonitrile activated carbon fiber.
[0060] A third aspect of the present invention provides a polyacrylonitrile activated carbon fiber prepared by the method described in the second aspect of the present invention;
[0061] The specific surface area of the polyacrylonitrile activated carbon fiber is 900-2900 m². 2 / g; the single filament strength loss rate of the polyacrylonitrile activated carbon fiber is 0.3%-4% of the single filament strength of the polyacrylonitrile carbon fiber.
[0062] Furthermore, the specific surface area of the polyacrylonitrile activated carbon fiber is 1000-2900 m². 2 / g; the single filament strength loss rate of the polyacrylonitrile activated carbon fiber is 0.3%-2% of the single filament strength of the polyacrylonitrile carbon fiber.
[0063] In this invention, the polyacrylonitrile carbon fiber refers to polyacrylonitrile carbon fiber prepared by high-temperature carbonization without acid treatment and supercritical carbon dioxide treatment.
[0064] The fourth aspect of this invention provides an application of the polyacrylonitrile activated carbon fiber described in the third aspect in the field of adsorption.
[0065] The present invention will be described in detail below through embodiments. In the following embodiments,
[0066] Specific surface area and pore volume were determined by nitrogen adsorption / desorption testing of activated carbon fibers using a JW-BK222 fully automated physical adsorption analyzer. Before testing, the samples were degassed under vacuum at 250℃ for 2-3 hours to remove gases and impurities from the pores. Using nitrogen as the adsorbate, the amount of nitrogen adsorbed was measured at 77K within a relative pressure range (P / P0) of 0-1, yielding the adsorption / desorption isotherm of the activated carbon fibers. Based on this isotherm, the specific surface area was calculated using the Brunauer-Emmett-Teller (BET) method. The total pore volume (Vtot) was determined using the amount of N2 adsorbed when the relative pressure was close to 1 (P / P0 = 0.99).
[0067] The mechanical properties of the fibers were determined by recording the stress-strain curves of individual fibers using an XQ-2 tensile testing instrument with a gauge length of 20 mm and a tensile rate of 20 mm / min. -1 At least 30 valid data points were obtained from each sample, and the average tensile strength N1 of the polyacrylonitrile activated carbon fiber was calculated; the average tensile strength N2 of the polyacrylonitrile carbon fiber was determined and calculated using the same method; the formula for calculating the single filament strength loss rate is: (N2-N1) / N2×100%.
[0068] All other raw materials are commercially available products.
[0069] Example 1
[0070] S1. Polyacrylonitrile fibers were prepared by wet spinning of DMSO / polyacrylonitrile spinning solution with a solid content of 20wt%. The spinneret orifice diameter was 0.055mm and the number of spinneret orifices was 3000. The solution was passed through a coagulation bath with a coagulation bath temperature and concentration of 0℃ and 12% respectively. The hot drawing process was carried out in 94℃ hot water with a hot drawing ratio of 10 to obtain polyacrylonitrile fibers.
[0071] S2. The polyacrylonitrile fiber is pre-oxidized in an oxidation furnace in four temperature zones: the first temperature zone is 220℃ for 10 min; the second temperature zone is 235℃ for 10 min; the third temperature zone is 255℃ for 15 min; and the fourth temperature zone is 275℃ for 11 min, to obtain pre-oxidized fiber. The pre-oxidized fiber is then subjected to low-temperature carbonization, with the temperature increased from 300℃ to 800℃ at a rate of 10℃ / min, to obtain low-temperature carbon fiber.
[0072] S3. The low-temperature carbon fiber is soaked in a hydrochloric acid solution with a concentration of 0.2 g / mL for 5 h, and then placed in a reaction vessel. CO2 is introduced into the reaction vessel at 60 °C to purge air twice, and CO2 is continuously introduced until the pressure in the reaction vessel is 10 MPa. After treatment for 20 min, the pressure is released for 2 min to obtain polyacrylonitrile activated low-temperature carbon fiber.
[0073] S4. The polyacrylonitrile activated low-temperature carbon fiber is heated to 1200℃ at a heating rate of 30℃ / min under N2 atmosphere protection to obtain polyacrylonitrile activated carbon fiber.
[0074] Example 2
[0075] The method is the same as in Example 1, except that in step S3, the concentration of the hydrochloric acid solution is 1 g / mL.
[0076] Example 3
[0077] The method is the same as in Example 1, except that in step S3, the concentration of the hydrochloric acid solution is 2 g / mL.
[0078] Example 4
[0079] The method is the same as in Example 1, except that in step S3, the concentration of the hydrochloric acid solution is 3 g / mL and the soaking time is 8 h.
[0080] Example 5
[0081] The method is the same as in Example 1, except that in step S3, the concentration of the hydrochloric acid solution is 3 g / mL and the soaking time is 16 h.
[0082] Example 6
[0083] The method is the same as in Example 5, except that in step S3, CO2 is introduced into the reactor at 130°C.
[0084] Example 7
[0085] The method is the same as in Example 5, except that in step S3, CO2 is introduced into the reactor twice at 130°C to purge air. CO2 is then continuously introduced until the reactor pressure reaches 18 MPa.
[0086] Example 8
[0087] The method is the same as in Example 5, except that in step S3, CO2 is introduced into the reactor twice at 130°C to purge air. CO2 is then continuously introduced until the reactor pressure reaches 18 MPa. The pressure is released after 50 minutes of treatment.
[0088] Example 9
[0089] The method is the same as in Example 5, except that:
[0090] In step S3, CO2 is introduced into the reactor twice at 130°C to purge air. CO2 is then continuously introduced until the reactor pressure reaches 18 MPa, and the pressure is released after 50 minutes.
[0091] In step S4, the temperature is increased to 1600°C at a heating rate of 30°C / min under N2 atmosphere protection.
[0092] Example 10
[0093] The method is the same as in Example 1, except that the concentration of the hydrochloric acid solution is 1 g / mL and the soaking time is 8 h.
[0094] Example 11
[0095] The method is the same as in Example 1, except that the concentration of the hydrochloric acid solution is 1 g / mL and the soaking time is 18 h.
[0096] Example 12
[0097] The method is the same as in Example 5, except that CO2 is introduced into the reactor at 50°C.
[0098] Example 13
[0099] The method is the same as in Example 5, except that CO2 is continuously introduced until the pressure in the reactor reaches 20 MPa.
[0100] Example 14
[0101] The method was the same as in Example 1, except that the concentration of the hydrochloric acid solution was 5 g / mL, the soaking time was 5 h, and CO2 was continuously introduced at 40 °C until the pressure in the reactor reached 7.5 MPa.
[0102] Example 15
[0103] The method of Example 5 is followed, wherein the hydrochloric acid solution is replaced with an equimolar amount of citric acid.
[0104] Comparative Example 1
[0105] The difference from Example 1 is that only acid treatment was performed, without supercritical carbon dioxide treatment.
[0106] Test case
[0107] The specific surface area and mechanical properties of the polyacrylonitrile activated carbon fibers prepared in the examples and comparative examples were tested, and the results are shown in Table 1.
[0108] Table 1
[0109] Example 1 936 0.56 0.21 Example 2 1097 0.58 0.35 Example 3 1321 0.64 0.56 Example 4 1692 0.68 0.71 Example 5 2537 0.82 1.83 Example 6 2603 0.82 1.89 Example 7 2698 0.83 1.92 Example 8 2801 0.84 1.97 Example 9 2812 0.84 1.98 Example 10 1586 0.65 0.61 Example 11 1050 0.68 0.75 Example 12 2416 0.82 1.79 Example 13 2385 0.81 1.69 Example 14 892 0.52 3.46 Example 15 2893 0.85 2.01 Comparative Example 1 689 0.42 10.12
[0110] As can be seen from Table 1, the polyacrylonitrile activated carbon fibers prepared in this application can achieve a strength of not less than 850 m² while ensuring a single filament strength loss rate of not more than 4%. 2 Specific surface area per g.
[0111] Further preferred embodiments 4-10 and 15 can achieve a strength of not less than 1500m while ensuring that the monofilament strength loss rate is not higher than 2%. 2 Specific surface area per g.
[0112] To further test the adsorption performance of the prepared polyacrylonitrile activated carbon fibers, an adsorption performance test was conducted: 0.2 g of the polyacrylonitrile activated carbon fibers prepared in the examples and comparative examples were weighed and placed in a 500 mL Erlenmeyer flask. 250 mL of a 20 mg / L Pb solution (water temperature 20℃, solution pH 5.17) was added to the flask, the flask was sealed, and the mixture was stirred at medium speed with a magnetic stirrer for 1 hour. After filtration, the Pb concentration in the filtrate was determined by flame atomic absorption spectrometry. The results are shown in Table 2.
[0113] Table 2
[0114] Example 1 6.01 Example 2 7.12 Example 3 8.43 Example 4 10.85 Example 5 16.05 Example 6 16.32 Example 7 16.96 Example 8 17.54 Example 9 17.59 Example 10 10.45 Example 11 6.13 Example 12 15.43 Example 13 15.31 Example 14 5.61 Example 15 18.29 Comparative Example 1 4.37
[0115] The results above show that Examples 1-15 of the present invention have good effects, and the specific surface area of the prepared polyacrylonitrile activated carbon fibers is relatively high, not less than 850 m². 2 / g, while its monofilament strength loss rate is no higher than 4%, and it has a high adsorption capacity.
[0116] Among them, the preferred embodiments 4-10 and 15 achieved significantly better results, with high specific surface areas of polyacrylonitrile activated carbon fibers, not less than 1500 m². 2 / g, while its monofilament strength loss rate is not higher than 2%, and its adsorption capacity is not less than 10mg / g.
[0117] In Examples 1-3, the concentration of the acid solution and the soaking time did not meet the preferred range, resulting in a low specific surface area of the polyacrylonitrile activated carbon fibers. In Example 11, even though the concentration of the acid solution met the preferred requirements, the excessively long acid treatment time also easily led to a low specific surface area of the polyacrylonitrile activated carbon fibers. In Examples 12-13, the supercritical CO2 treatment conditions did not meet the preferred range, resulting in a low specific surface area of the polyacrylonitrile activated carbon fibers. In Example 14, because the acid treatment and supercritical CO2 treatment conditions did not meet the scope of this invention, the specific surface area of the polyacrylonitrile activated carbon fibers was very low, and the monofilament strength loss rate was also high.
[0118] The preferred embodiments of the present invention have been described in detail above; however, the present invention is not limited thereto. Within the scope of the inventive concept, various simple modifications can be made to the technical solutions of the present invention, including combinations of various technical features in any other suitable manner. These simple modifications and combinations should also be considered as the content disclosed in the present invention and are all within the protection scope of the present invention.
Claims
1. A method for activating polyacrylonitrile activated low-temperature carbon fibers, characterized in that, The method includes: Polyacrylonitrile spinning solution is spun to obtain polyacrylonitrile fibers. The polyacrylonitrile fibers are then subjected to pre-oxidation and low-temperature carbonization to obtain low-temperature carbon fibers. The low-temperature carbon fibers are then acid-treated to obtain pretreated activated low-temperature carbon fibers. Finally, the pretreated activated low-temperature carbon fibers are treated with supercritical carbon dioxide to obtain activated low-temperature polyacrylonitrile carbon fibers. The acid treatment includes: contacting low-temperature carbon fibers with an acid solution; The concentration of the acid solution is 0.1-3 g / mL; The conditions for supercritical carbon dioxide treatment include: a temperature of 50-140℃, a pressure of 8-20MPa, and a time of 10-50min. The supercritical carbon dioxide treatment is carried out in a reactor. The method further includes: purging the reactor before supercritical carbon dioxide treatment; The method further includes: depressurizing the reactor after supercritical carbon dioxide treatment.
2. The activation method according to claim 1, wherein, The contact conditions include: a contact temperature of 5-35℃ and a contact time of 5-18h.
3. The activation method according to claim 2, wherein, The contact conditions include: a contact temperature of 10-30℃ and a contact time of 8-16h.
4. The activation method according to any one of claims 1-3, wherein, The acid solution is selected from inorganic acid solutions and / or organic acid solutions.
5. The activation method according to claim 4, wherein, The inorganic acid solution is a hydrochloric acid solution and / or a phosphoric acid solution.
6. The activation method according to claim 4, wherein, The organic acid solution is citric acid.
7. The activation method according to any one of claims 1-3, wherein, The concentration of the acid solution is 1-3 g / mL.
8. The activation method according to claim 1, wherein, The conditions for supercritical carbon dioxide treatment include: a temperature of 50-130℃, a pressure of 10-20MPa, and a time of 20-50min.
9. The activation method according to claim 1, wherein, The conditions for the venting process include: passing supercritical carbon dioxide into the reactor 2-5 times.
10. The activation method according to claim 9, wherein, The conditions for the venting process include: passing supercritical carbon dioxide into the reactor 3-4 times.
11. A method for preparing polyacrylonitrile activated carbon fibers, characterized in that, The method includes: S1. Polyacrylonitrile spinning solution is spun to obtain polyacrylonitrile fibers, and the polyacrylonitrile fibers are subjected to pre-oxidation treatment and low-temperature carbonization treatment to obtain low-temperature carbon fibers. S2. Activate the low-temperature carbon fiber to obtain polyacrylonitrile activated low-temperature carbon fiber; S3. The polyacrylonitrile activated low-temperature carbon fiber is subjected to high-temperature carbonization treatment to obtain the polyacrylonitrile activated carbon fiber. The high-temperature carbonization treatment is carried out in a protective atmosphere. In step S2, the activation method is the activation method described in any one of claims 1-10.
12. The method according to claim 11, wherein, The pre-oxidation process includes passing the polyacrylonitrile fiber through multiple temperature zones for stepped heating treatment.
13. The method according to claim 12, wherein, The polyacrylonitrile fiber passes through four temperature zones, namely a first temperature zone, a second temperature zone, a third temperature zone, and a fourth temperature zone.
14. The method according to claim 13, wherein, The temperature of the first temperature zone is 210-230℃, the temperature of the second temperature zone is 225-245℃, the temperature of the third temperature zone is 245-265℃, and the temperature of the fourth temperature zone is 265-285℃.
15. The method according to claim 14, wherein, The pre-oxidation time in the first temperature zone is 8-12 min, the pre-oxidation time in the second temperature zone is 9-13 min, the pre-oxidation time in the third temperature zone is 13-15 min, and the pre-oxidation time in the fourth temperature zone is 10-15 min.
16. The method according to any one of claims 11-15, wherein, The conditions for the low-temperature carbonization treatment include: a temperature of 300-800℃ and a heating rate of 5-10℃ / min.
17. The method according to claim 16, wherein, The conditions for the low-temperature carbonization treatment include: a temperature of 400-800℃ and a heating rate of 6-9℃ / min.
18. The method according to claim 11, wherein, The conditions for high-temperature carbonization include: a temperature of 1200-1600℃ and a heating rate of 5-30℃ / min.
19. Polyacrylonitrile activated carbon fibers prepared by the method according to any one of claims 11-18.
20. The polyacrylonitrile activated carbon fiber according to claim 19, wherein, The specific surface area of the polyacrylonitrile activated carbon fiber is 900-2900 m². 2 / g; the single filament strength loss rate of the polyacrylonitrile activated carbon fiber is 0.3%-4% of the single filament strength of the polyacrylonitrile carbon fiber.
21. The application of the polyacrylonitrile activated carbon fiber according to claim 19 or 20 in the field of adsorption.
Citation Information
Patent Citations
Method for preparing active carbon fiber material with energy storage characteristic from polyacrylonitrile-based pre-oxidized fiber and application of active carbon fiber material
CN103409853A
Preparation method of polyacrylonitrile-based active carbon fibers and application of active carbon fibers
CN106676676A
Method for preparing super activated carbon by utilizing modification supercritical oxidation technology
CN102139875A
Method for preparing activated carbon fibers based on centrifugal spinning method
CN110485001A